THE INFLUENCE OF PRODUCT INNOVATION AND SOCIAL MEDIA MARKETING ON CUSTOMER SATISFACTION THROUGH PURCHASE DECISIONS IN THE KOREAN FOOD INDUSTRY (A STUDY ON DAEBAG.E PRODUCTS) - Prisca Anjalini Dumatubun; Damelina Basauli Tambunan (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to examine the influence of Product Innovation and Social Media Marketing on Customer Satisfaction through Purchase Decisions in the Korean food industry, specifically focusing on Daebag.e. Method: A quantitative research method was employed, utilizing a survey with a purposive sampling technique involving 47 respondents who have made repeat purchases of Daebag.e products in Surabaya and Sidoarjo. Data were collected using a structured questionnaire measured with a Likert Scale, and analyzed using the Partial Least Square Method with SmartPLS 4.0. Results: The findings indicate that Product Innovation significantly impacts Customer Satisfaction and Purchase Decisions. Similarly, Social Media Marketing positively influences Customer Satisfaction and Purchase Decisions. Furthermore, Purchase Decisions mediate the relationship between Product Innovation, Social Media Marketing, and Customer Satisfaction. Novelty: This study provides a comprehensive understanding of how Purchase Decisions act as a mediating variable, enhancing the impact of Product Innovation and Social Media Marketing on Customer Satisfaction within the Korean food industry context, particularly for the Daebag.e brand, which has been less explored in existing literature.